Pendampingan Pembuatan Nomor Induk Berusaha (NIB) Menggunakan Website Online Single Submission (OSS) pada UMKM di Desa Purwosari, Comal, Kabupaten Pemalang - Agelia, Ela; Safitri, Rizki Ananda; Widyastuti, Tri Ayu; Mubarok, M. Sultan; Gunawan, Ade (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
This service aims to provide understanding to business actors about the importance of business permits, especially the Business Identification Number (NIB), in accordance with government regulations regarding online single submission (OSS) in Government Regulation Number 24 of 2018. The service method involves observation, interviews, and counseling. , where the team provides an explanation regarding NIB to business actors. The results of the service show that public interest in managing NIB is still low, so wider outreach efforts are needed to increase understanding and awareness among MSME owners about the importance of NIB in carrying out business activities. It is important to ensure that MSMEs can operate legally and effectively to support economic growth and the equal distribution of prosperity in Indonesia.